A mass-conserving lattice Boltzmann method for bubble behavior estimation. (16th January 2019) - Li, Xue; Gao, Deyang; Hou, Baolin; Wang, Xiaodong
Highlights: The behavior of bubble rising in viscous liquid was numerically studied. A mass-conserving LBM model was developed for gas–liquid two phase flow. Physical accuracy and numerical stability were ensured. Gas-liquid bubble closures were obtained by 3D simulations. Abstract: The Lattice Boltzmann Method (LBM) has been known as a promising approach for simulating the deformable moving interface of multiphase fluid phenomena due to its mesoscopic nature in organizing and executing distribution functions. However, LBMs are limited in simulating real gas–liquid bubbly flows, where the numerical inaccuracy and instability may significantly increase due to the high surface tension force and the large density ratio. In this paper, a mass-conserving LBM model is developed. The proposed model introduces a conserving correction step and an effective surface tension formula to improve physical accuracy, and utilizes a Multiple-Relaxation-Time (MRT) D3Q19 (three-dimensional and 19 discrete direction) operator to increase numerical stability. The proposed model was applied to estimate bubble behaviors, dimensionless parameter correlations, and drag force coefficient. The results were compared with analytical results, existing numerical results, and experimental data in literature and performed. The good agreement indicates that the proposed mass-conserving LBM model has the ability to predict bubble behaviors in the gas–liquid system.